Comment on 'Counting the World's Poor' by Angus Deaton - Srinivasan, T.N. (Washington, DC: World Bank, 2014)
Deaton s analysis of the problems with poverty counts and suggestions for improvement, including issues needing further research, are based on two distinct stages in counting the poor. At the first or international stage, a world poverty line is set and used to derive comparable poverty lines for each country. At the second or domestic stage, the poverty lines are used to count the number of poor people in each country, and the others are added up over countries. He finds disquieting evidence about both stages of counting. The data for poverty counts in the second stage come from household surveys, whereas data on aggregate economic growth are from National Accounts Statistics (NAS). Deaton finds that in many countries there are large and growing disparities between survey data and national accounts so that there is no consistent empirical basis for conclusions about the extent to which growth reduces poverty. It is scandalous that even after nearly half a century of pursuing national and international programs for the eradication of mass poverty, the empirical foundations for assessing the success or failure of the programs and drawing lessons from them are so weak as to be deemed nonexistent. Abandoning them and focusing on national and subnational poverty analysis that goes beyond headcounts will be the sensible course to follow. The author focuses only on consumption-based poverty lines. The reason is the challenge of defining household income in a theoretically satisfactory manner and collecting data on income based on that definition through household surveys in any country (developed or developing). Deaton (1989) discusses the difficulties in meeting the challenge. Poverty counts based on income-based poverty lines are even more problematic than consumption-based ones.